Analisis Kebutuhan Guru Dan Siswa Terhadap Pengembangan Bahan Ajar Lembar Kerja Peserta Didik Elektronik (E-Lkpd) Ipa Berbasis Liveworksheet Dengan Model Problem Based Learning - Dwi Ummu, Aulia; Herlina Usman (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
This research aims to analyze the needs of teachers and students in developing liveworksheet-based Electronic Science Student Worksheets using a Problem Based Learning (PBL) approach in an elementary school environment on the subject of light and sound (Seeing because of Light, Hearing because of Sound) for class V. Qualitative descriptive research with the ADDIE development model which consists of five stages, namely Analyze, Design, Development, Implementation, and Evaluation. In the needs analysis, the research subjects were 47 students and 2 class teachers. The data collection techniques used were interviews and questionnaires to collect data resulting from needs analysis. The research results show that the teaching materials used by 2 teachers are still monotonous/lack of variety. From the research results, it can be concluded that the live worksheet-based Electronic Science Student Worksheet using the Problem Based Learning (PBL) approach to light and sound can be used as a learning medium..